2020
DOI: 10.3174/ajnr.a6412
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Thrombectomy of Calcified Emboli in Acute Ischemic Stroke: A Multicenter Study

Abstract: BACKGROUND AND PURPOSE: Large intracranial vessel occlusion due to calcified emboli is a rare cause of major stroke. We assessed the prevalence, imaging appearance, the effectiveness of mechanical thrombectomy, and clinical outcome of patients with large-vessel occlusion due to calcified emboli. MATERIALS AND METHODS:We performed a retrospective analysis of clinical and procedural data of consecutive patients who underwent mechanical thrombectomy due to calcified emboli in 7 European stroke centers. RESULTS:We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…No specific target vessel occlusion side, which involved the basilar artery in all cases in this cohort, was associated with a higher risk of MT failure. Corresponding to studies of the anterior circulation, further investigation is needed to identify probable associations of thrombus length or texture and MT failure [21,22]. Overall, a sufficient recanalization result for stroke patients and MT of the posterior circulation was achieved in 86.2%, which is comparable to the 90.3% and 84.5% success rate of MT in basilar artery occlusions published by Meinel et al and Sun et al, respectively, and underlines the notion that success rates for MT in the posterior circulation are comparable to the anterior circulation [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…No specific target vessel occlusion side, which involved the basilar artery in all cases in this cohort, was associated with a higher risk of MT failure. Corresponding to studies of the anterior circulation, further investigation is needed to identify probable associations of thrombus length or texture and MT failure [21,22]. Overall, a sufficient recanalization result for stroke patients and MT of the posterior circulation was achieved in 86.2%, which is comparable to the 90.3% and 84.5% success rate of MT in basilar artery occlusions published by Meinel et al and Sun et al, respectively, and underlines the notion that success rates for MT in the posterior circulation are comparable to the anterior circulation [16,23].…”
Section: Discussionmentioning
confidence: 99%
“…ET has been suggested as an alternative therapy, although no definite treatment guidelines have been established. One retrospective multicenter study of 40 patients with CCE who underwent ET reported modified thrombolysis in cerebral infarction score of >2b in 57.5% of patients and excellent outcome (mRS 0-1) in 20.6% of patients [ 2 ]. Co-administration of tPA did not lead to better outcomes or more complications [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…One retrospective multicenter study of 40 patients with CCE who underwent ET reported modified thrombolysis in cerebral infarction score of >2b in 57.5% of patients and excellent outcome (mRS 0-1) in 20.6% of patients [ 2 ]. Co-administration of tPA did not lead to better outcomes or more complications [ 2 ]. However, patients who underwent ET may have worse angiographic outcomes and a higher mortality rate when compared with noncalcified thrombi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 16 Calcified emboli are quite rare in AIS patients with large vessel occlusions, but when present, calcification is associated with poor recanalisation and higher mortality. 52 The presence of atheromatous gruel also showed a negative correlation with successful EVT recanalisation. 10 Funatsu et al found a trend suggesting the presence of vascular wall components was associated with lesser recanalisation success.…”
Section: Endovascular Treatmentmentioning
confidence: 94%